Development of three-dimensional resiliency theory in solving mathematical problem - Callaman, Roar; Palompon, Daisy (Journal of Education and Learning (EduLearn), 2026)
This study aims to develop a theory to understand how students cultivate and apply resilience in solving mathematical problems. Specifically, it integrates cognitive, emotional, and social dimensions of resilience to create a holistic framework. Using a deductive theory development approach, the study starts with an existing theory, formulates hypotheses, and tests them through data collection and analysis. Seven axioms were formulated leading to three propositions: i) students with higher levels of mathematics resilience will demonstrate greater persistence and effort when faced with challenging mathematical problems; ii) psychological, cognitive and social factors are influential to a student’s resilience in solving mathematical problems; and iii) developing a growth attitude, fostering a supportive learning environment, and providing appropriate teacher scaffolding can help all to build mathematical resilience and problem-solving success. From these propositions, the three-dimensional resilience theory in mathematical problem solving is formulated. This theory recognizes the interplay of psychological, social, and cognitive factors. Future research could focus on testing it in various educational settings, such as different grade levels, cultural contexts, or educational systems, to assess its generalizability and robustness.